Serum concentrations of perfluorinated alkyl substances in farmers living in areas affected by water contamination in the Veneto Region (Northern Italy). (March 2020) - Ingelido, Anna Maria; Abballe, Annalisa; Gemma, Simonetta; Dellatte, Elena; Iacovella, Nicola; De Angelis, Giovanna; Marra, Valentina; Russo, Francesca; Vazzoler, Marina; Testai, Emanuela; De Felip, Elena
Graphical abstract: Highlights: Exposure of farmers living in PFAS contaminated areas was investigated. PFAS levels in farmers were higher than in exposed from general population. Main factor influencing PFAS serum concentrations was water contamination of the residence area. Gender, years of residence, well water use and own produced food consumption influenced PFAS concentrations. PFOA was detected at the highest concentrations. Abstract: Human exposure to per- and polyfluorinated alkyl substances (PFASs) is a major public health concern because in the last decades several cases of overexposure of people to PFASs, in particular through contaminated water, occurred worldwide. In 2013–2017 a PFAS drinking water contamination was discovered and investigated in northern Italy (Veneto region) and high PFAS serum levels were detected in exposed people. 629 subjects were enrolled: 257 residing in municipalities in the areas under impact, 250 residing in municipalities in areas at presumed background exposure and 122 farmers living in contaminated rural areas producing and consuming own livestock and vegetables and frequently using well water. The highest PFAS serum concentrations (median PFOA concentrations 40 ng/g) were found in the subgroup of farmers. The main factors influencing PFAS serum levels of farmers were residence area and the related extent of drinking water contamination, gender, years of residence in the municipalities, well water consumption and consumption of own produced food. PFOA serum concentrations in farmers residing in the areas of the Veneto region impacted by PFAS contamination are among the highest found worldwide.